Health Education Specialists: Professional Practice During a Pandemic. Issue 2 (March 2023) - Kerr, Dianne; Haider, Salma; Hancher-Rauch, Heidi; Blavos, Alexis; Brookins-Fisher, Jodi; Thompson, Amy; Glunz, Carly
Authors conducted survey research on Health Education Specialists' (HES) involvement in the COVID-19 pandemic. Participants ( n = 1, 837) completed questions on COVID-19 work and job responsibilities, use of the NCHEC Areas of Responsibility and Competencies in addressing the pandemic, education and training, work with populations at risk, and volunteer work related to COVID-19. The majority of respondents reported some work, either professional or personal associated with the pandemic, and the majority felt prepared to do this work, although it caused additional work responsibilities with no additional pay. Many had to work from home during the pandemic, using technology to accomplish their tasks. Most reported conducting education and prevention and designing and implementing communication strategies regarding the pandemic. Those with MCHES® certification were more likely to use the HESPA-II 2020 competencies in their work and more likely to perform listed COVID-19 activities, with the exception of contact tracing and direct care to COVID-19 patients, which were more likely conducted by CHES® certified HES. Results of this study show the significant level of involvement of HES in the COVID-19 pandemic in a variety of roles and capacities, despite a challenging political landscape during the time the survey was administered. Many HES reported volunteer work in addition to their paid work, including donating money, distributing food, or making masks. Finally, HES welcomed more training on COVID-19 and use of technology. Results of the study may be used to document the roles of HES during the COVID-19 pandemic and to make recommendations for future emergency preparedness efforts.